THE ADAPTATION OF GOND ART AESTHETICS FOR CONTEMPORARY TOURISM POSTERS - Banthia, Prashasti; Bharadwaj, Kumkum (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper analyses the convergence of visual cultural traditions of gond art and contemporary digital posters used for Madhya Pradesh tourism publicity. The study highlights how often the designers have been using these aesthetic art motifs to raise awareness of tourism, culture and heritage because of the gradual shifting focus of the global tourism sector towards authentic cultural immersion. However this approach upraised the crucial issues concerning the intersection of artistic tribute, publicity and the ethics of taking cultural elements for profit purpose. From some selected contemporary tourism e-posters issued by government departments of culture and tourism of Madhya Pradesh, the qualitative visual analysis help to recognize the use of gond art appropriate for contemporary advertisements. This paper focuses on the use of beautiful gond painting motifs especially the Tree of Life, ornate details like flora, fauna and such other intricate patterns as a commercial tool to drew travellers globally; how these traditional paintings their themes, colour schemes and patterns are modified for contemporary digital screen; the ethical tension between protecting indigenous cultural aesthetics and their use as commercial product. The research suggests that while the use of gond art in publicity posters work as both for a preserving traditional art form and advanced advertising design plan, they often have risk to misinterpret the original narrative idea of the artwork. The paper concludes by recommending a collaborative design plan that ensures the indigenous artisans to guide how their visual heritage authentic artwork is represented, interpreted and used in global tourism industry.